PEMBELAJARAN MATEMATIKA MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA : KAJIAN META ANALISIS (IKIP Siliwangi, 2021)
This study aims to determine which types of approaches, levels of education and learning materials are effective when applying the Discovery Learning model to students' creative thinking skills in learning mathematics. The research method is a meta-analysis study of 9 (nine) studies in national journals from 2015-2021 (June) with data collection techniques using Non-probability Sampling and data processing begins with data collection, coding, editing and tabulation. Meta-analysis research shows that learning mathematics using the Discovery Learning model is more effective when applied using a scientific approach at the junior high school level with learning materials for spatial structures.